Does the patient’s physical activity affect the course of cardiac surgery - a comprehensive approach to cardiac surgery patients - Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Koszyczarek, Karolina; Marańska, Diana (Quality in Sport, 2024)
Cardiovascular diseases represent a leading cause of morbidity worldwide. Over the past years, the field of cardiac surgery has significantly evolved. Globally, more than 2 million cardiac surgeries are performed annually. Among the main procedures are coronary artery bypass grafting (CABG), valve replacements, and heart transplants. The increasing number of patients requiring such treatment and, consequently, the rising number of procedures performed imply an improvement in their quality. With advancements in surgical techniques, the scope of patients eligible for procedures has also expanded. Patients undergoing cardiac surgeries are increasingly older and often suffer from significant comorbidities, such as hypertension and diabetes. Effective cardiac surgery significantly enhances the quality of life. When caring for a patient undergoing cardiac surgery, many aspects of the patient need to be considered to approach them holistically, while simultaneously creating an individualized treatment pathway. Not only the cardiac aspect but also various other factors need to be taken into account, including the patient’s diet, medications, comorbidities, mental state, and physical activity. In this work, we emphasize the role of both postoperative and preoperative care for cardiac surgery patients, which, when properly executed, can be the key to the patient’s recovery.